Collagenase in Dupuytren Disease (Springer International Publishing, 2018)
This book offers detailed guidance on the use of collagenase, or enzymatic fasciotomy, as a nonsurgical treatment for Dupuytren's contracture and explains its role in relation to the other forms of treatment, including open fasciectomy, needle aponeurotomy, and lipofilling. Clear guidance is provided on technique, current indications, and off-label usage. With the help of tips and tricks from leading experts, the reader will learn how to personalize the procedure to meet the needs of individual patients. Advice is also provided on all aspects of rehabilitation, which is a key determinant of treatment outcome. Collagenase treatment of Dupuytren's disease has the benefits of low invasiveness and rapid patient recovery and achieves reasonable recurrence-free periods. It is especially valuable in patients with rapid recurrence following surgery. In documenting and appraising every aspect of its use, this book will be of value for all who treat patients with Dupuytren's disease, including hand surgeons, orthopedists, plastic surgeons, physiatrists, and physiotherapists.